Impact of Source to Substrate Distance on the Properties of Thermally Evaporated CdS Film - Dey M.; Das N.K.; Dey M.; Farhad S.F.U.; Matin M.A.; Amin N. (Gazi Universitesi, 2023)
Borosilicate glass; Glass substrates; Hall mobility; II-VI semiconductors; Infrared devices; Near infrared spectroscopy; Optical properties; Thermal evaporation; Thin films; Vacuum evaporation; X ray diffraction; CdS films; Deposited films; HEMS; Optical and electrical properties; Property; Source to substrate distances; Thermal evaporator; Thin-films; UV-vis-NIR; XRD; Cadmium sulfide